Dual Effects of Hypoxia-Inducible Factors-1 Alpha in Bleomycin-Induced Pulmonary Fibrosis Treated by Human Umbilical Cord Mesenchymal Stem Cells - Hongpeng Zhang; Hao Wang; Yong Xia; Nianmin Qi (Stem Cells International)
Pulmonary fibrosis (PF) is a kind of lung disease characterized by scar formation and inflammation damage. Mesenchymal stem cells (MSCs) are considered a promising therapy because of multidirectional differentiation and immune regulation. Our research was designed for identifying the preventative defensive ability and therapeutic effect of human umbilical cord mesenchymal stem cells (HUCMSCs). HUCMSCs were administered before or after bleomycin injection in different groups of C57BL/6 mice. We calculated the survival time of mice, the lung coefficients, contents of hydroxyproline, and pathological scores. The expression levels of HIF-1α (hypoxia-inducible factor-1α), α-SMA (α-smooth muscle actin), γH2AFX (γH2A histone family, member X), ZO-1 (zonula occludens-1), ROS (reactive oxygen species) content, and proliferation ability of A549 cells were detected after treatment with bleomycin and HUCMSCs conditioned medium (HUCMSCs-CM), respectively, or together in vitro. In addition, we examined the secretome of HUCMSCs in regular and inflammatory stimulation conditions. Our results demonstrated that prophylactic HUCMSC administration before bleomycin-induced modeling process could significantly meliorate damage to pulmonary fibrosis. After the deletion of HIF-1α, damage markers in A549 cells were significantly reduced in therapeutic administration condition. However, it was the opposite in prophylactic administration condition. The results confirmed that HUCMSCs had available preventive effect on bleomycin-induced pulmonary fibrosis in vivo and in vitro. However, it may have a negative effect in therapeutic administration condition because of the dual effect of HIF-1α.